40Ar/39Ar geochronology reveals rapid change from plume‐assisted to stress‐dependent volcanism in the Newer Volcanic Province, SE Australia. (21st March 2017) - Oostingh, K. F.; Jourdan, F.; Matchan, E. L.; Phillips, D.
Abstract: Here we present 40 Ar/ 39 Ar ages of volcanic features in the Cenozoic intraplate Newer Volcanic Province in southeast Australia. The <5 Ma volcanic products in the Newer Volcanic Province can be subdivided into tholeiitic, valley‐filling Newer Plains basalts, and alkaline scoria cones, lava shields, and maars of the Newer Cones series. Plateau ages range from 3.76 ± 0.01 to 4.32 ± 0.03 Ma (2σ; all sources of uncertainties included) for the Newer Plains series, with production rates of volcanism decreasing post 4 Ma. We suggest that magmatism is related to the complex interplay of magma upwelling due to edge‐driven convection and the Cosgrove track mantle plume located in the northeast of the province at 6.5–5 Ma. Plateau ages range from 1290 ± 20 to 41.1 ± 2.2 ka (2σ) for the Newer Cones series, with a diffuse age progression in the onset of volcanism for these features from east to west. Analyses of the distribution and geomorphology of these volcanic features indicates a strong control of basement faults on volcanism, reflected in alignment of volcanic features along Paleozoic north‐south oriented basement faults in the east and Cretaceous northwest‐southeast oriented extensional features in the west. This age progression can be explained by a westerly migration of stress derived from the left‐lateral strike‐slip Tasman Fracture Zone. This suggests that the general mechanism of volcanism changed from upwelling due to plume‐assisted edge‐driven convection prior to ∼4 Ma to stress‐dependent upwelling at around 1.3 Ma. Key Points: Varying production rates of >4 Ma volcanism in SE Australia suggests interplay between edge‐driven convection and the Cosgrove mantle plume Volcanism in the Newer Volcanic Province shows a strong spatial dependence on preexisting basement structures 40 Ar/ 39 Ar ages of <1 Ma volcanoes show a diffuse age trend from east to west, proposed to be caused by migrating stress across SE Australia